Sonocatalytic degradation of caffeine using cerium oxide: reaction kinetic studies / Aaron Michael and Nur Fadzeelah Abu Kassim - Aaron, Michael; Abu Kassim, Nur Fadzeelah (2020)
Two kinetic models were proposed which are apparent first order model and Langmuir-Hinshelwood model to compare the reaction kinetic. To obtain the apparent rate constant for Langmuir Hinshelwood and apparent first order, fitting was done by applying linear square regression method. The regression line obtained for Langmuir Hinshelwood model for sonocatalytic degradation of caffeine using cerium oxide without oxidant is 0.7823 and with oxidant is 0.9867, while the apparent rate constant, k app for apparent first order model for sonocatalytic degradation of caffeine using cerium oxide without oxidant is 0.9263 and with oxidant is 0.9934. The coefficient of determination (R²) values for each experiment conditions shows that the sonocatalytic degradation of caffeine followed more to apparent first order model since the regression value is closer to 1.